The intelligence of children with Reading Difficulties (RD) by Cognitive Assessment System (CAS) - Khaidzir Hj. Ismail; Ooi, Boon Keat (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
This case study discusses one of the latest technology based instrument, the Cognitive Assessment System (CAS) in assessing cognitive functioning of Luria‟s three functional units of brain or theoretical base of Planning, Attention, Simultaneous and Successive (PASS). CAS is capable of measuring not only the cognitive ability and process but also of determining intervention purposes for children with specific needs. Therefore, this study aims to examine the PASS cognitive functions and the use of CAS to subjects with Reading Difficulties (RD). Profiles of the CAS were firstly obtained from children with RD, and then the PASS scale standard scores were compared by using United State norms. The specific weakness of cognitive functioning was detected from the children with ESL reading difficulties. CAS was administered individually to 50 ESL poor achievers in standard 3 at Sekolah Rendah Kebangsaan Bandar Tun Hussein Onn (SRKBTHO). There were distinct PASS cognitive profiles among the poor achiever of ESL children and gender was not the determinant. The PASS scale standard scores showed 41% (n=20) is at average level, 30% (n=16) at low average level, 26% (n=13) at below average level and only 2% (n=1) at well below average level. There was no significant difference between girls and boys in term of cognitive processing. However, the poor achievers of English as Second Language (ESL) children were significantly low for simultaneous processing which is highly related to the ability of comprehension